Arduino and Kinect projects design, build, blow their minds - Melgar, Enrique Ramos (Apress, 2012)
If you've done some Arduino tinkering and wondered how you could incorporate the Kinector the other way aroundthen this book is for you. The authors of Arduino and Kinect Projects will show you how to create 10 amazing, creative projects, from simple to complex. You'll also find out how to incorporate Processing in your project designa language very similar to the Arduino language. The ten projects are carefully designed to build on your skills at every step. Starting with the Arduino and Kinect equivalent of "Hello, World," the authors will take you through a diverse range of projects that showcase the huge range of possibilities that open up when Kinect and Arduino are combined. Gesture-based Remote Control. Control devices and home appliances with hand gestures.  Kinect-networked Puppet. Play with a physical puppet remotely using your whole body.  Mood Lamps. Build your own set of responsive, gesture controllable LED lamps. Drawing Robot. Control a drawing robot using a Kinect-based tangible table.  Remote-controlled Vehicle. Use your body gestures to control a smart vehicle. Biometric Station. Use the Kinect for biometric recognition and checking Body Mass Indexes.  3D Modeling Interface. Learn how to use the Arduino LilyPad to build a wearable 3D modelling interface.  360º Scanner. Build a turntable scanner and scan any object 360º using only one Kinect.  Delta Robot. Build and control your own fast and accurate parallel robot.